Mestizaje as ethical disposition: indigenous rights in the neoliberal state. Issue 3 (1st September 2016) - Poole, Deborah
ABSTRACT: This article explores the modes of aspiration, skepticism, and suspicion that constitute the inheritance of mestizaje in neoliberal Peru. Drawing on recent controversies regarding the metrics deployed to determine access to indigenous rights, it argues for the need to move away from liberal understandings of mestizaje as a bounded 'identity' claim, to consider instead how the politics and discourse of mestizaje shape a more generalized affective politics of skepticism regarding all identity claims. More specifically, I argue that mestizaje acquires particular affective and ethical force in relation to the fiscal and technical norms that underwrite postregulatory government in Peru. What interests me in pursuing this argument is to understand how, in its move away from the forms of citizenship, constitutive rights, and recognition that fueled the liberal state, neoliberalism has simultaneously gained force from the ethos of suspicion that surrounds any claim to an antecedent or foundational (cultural, racial, or ethnic) identity, and forwarded new technologies of governance that render illegible emergent claims to national, territorial, or cultural 'rights' or 'identities'. In this article, I track this intersection of historical idioms of mestizaje and new technologies of government by looking at the technical instruments through which the Peruvian state sets out to reshape the territorial underpinnings of community and indigenous identity, and the implications of such technologies for the implementation of indigenous rights to prior consultation.